Thermo-sensitivity of hybrid nanogels for specific endogenous hydrogen sulfide detection and efficient flash chill treatment. Issue 29 (29th June 2021) - Sun, Xu-hao; Wang, Qiu-bo; Pan, Li; Mu, Yi-lin; Zhang, Xian; Liu, Zhao-e
Abstract : Thermo-responsive nanogels, poly(NIPAM–AAM) were prepared by a facile method of free radical one-pot precipitation based on monomeric N -isopropylacrylamide (NIPAM). Abstract : Thermo-responsive nanogels, poly(NIPAM–AAM) were prepared by a facile method of free radical one-pot precipitation based on monomeric N -isopropylacrylamide (NIPAM). At the same time, surface carboxyl group-modified fluorescent conjugated polymer nanoparticles (PNPs–COOH ) were immobilized in the nanogel networks by hydrogen bonding to show bright green photoluminescence and outstanding thermo-responsive properties with a typical two-phase Tai Chi structure. Poly(NIPAM–AAm)–PNPs–COOH displays a larger change of hydrodynamic diameter ( D h ) and a reversible volume transition from ∼150 nm at 40 °C to ∼1.0 μm at 4 °C. The change will cause apoptosis of cells to finish flash chill treatment. Meanwhile, the fluorescence of poly(NIPAM–AAm)–PNPs–COOH demonstrates reversible quenching and recovery with the expansion and collapse of the nanogel network induced by temperature changes. In addition, when adding Fe 3+, the fluorescence of poly(NIPAM–AAm)–PNPs–COOH can be quenched due to the chelation between the PNPs–COOH and Fe 3+ and then recovered in the presence of hydrogen sulfide because the chelate is broken; this was attributed to the stronger affinity between Fe 3+ and S 2− . Therefore, the fluorescence nanoplatform, Fe 3+ /poly(NIPAM–AAm)–PNPs–COOH, was successfully used to detect endogenous hydrogen sulfide in living A549 cells.